Midfoot arthrodesis. Issue 1 (March 2016) - Gougoulias, Nikolaos; Lampridis, Vasileios
Highlights: Midfoot arthrodesis union rate was 93%. 90% of patients rated their outcome as good or excellent. Complications occurred in 17% of patients. Unplanned surgical procedures were needed in 20% of patients. Orthotics was needed postoperatively in 34% of patients. Abstract: Background: Surgery for midfoot arthritis is challenging and technically demanding, especially in the presence of deformity. Methods: Thirty patients (30 feet) with symptomatic midfoot arthritis and deformities, underwent arthrodesis, along with adjuvant procedures to realign the hindfoot and forefoot where needed. Results: Union was achieved in 28 out of 30 (93.3%) patients. Mean time to union was 12.9 weeks (range 10–18). Five patients (16.6%) developed postoperative complications and six patients (20%) required unplanned surgical procedures. Orthotics was needed postoperatively in 14 patients (34%). Fourteen out of 30 patients rated their outcome as excellent (47%), 13 out of 30 as good (43%) and 3 out of 30 (10%) as fair or poor. Conclusions: Although the vast majority of patients rated their outcome as good or excellent, the foot is not completely normal, with residual pain from the adjacent joints, need for unplanned surgery and use of orthotics postoperatively.